Efficacy and safety of interferon-alpha 1b injection into the intervertebral foramen with ultrasonic guidance in patients with postherpetic neuralgia: study protocol for a randomized, double-blind, placebo-controlled, multicenter clinical trial - Hui-Min Hu; Hui-Min Hu; Wen-Hui Liu; Wen-Hui Liu; Chen Li; Chen Li; Qing Shi; Qing Shi; Chun-Hua Liu; Chun-Hua Liu; An-Xiang Liu; An-Xiang Liu; et al. (Frontiers in Neurology)
PurposePostherpetic neuralgia (PHN) is a type of refractory neuropathic pain that causes significant suffering, disability, economic loss, and medical burden. In this study, we aim to evaluate the efficacy and safety of interferon (IFN)-α1b injection into the intervertebral foramen of patients with PHN.Patients and methodsThis is a study protocol for a randomized, double-blind placebo-controlled multicenter clinical trial. A total of 200 participants with PHN from 11 hospitals will be recruited and randomly assigned to the treatment group administered with IFN-α1b and control group treated with placebo in a 1:1 ratio. Both groups will also receive oral pregabalin 150 mg twice daily and lidocaine injection into the intervertebral foramen as conventional therapy. This trial will involve a screening period, a 2-week intervention, and a 3-month follow-up. The primary outcomes will include the visual analog scale score and duration of pain relief. The secondary outcomes will include the 36-item short-form, dosage and duration of painkillers taken, viral load of varicella-zoster virus DNA, humoral cytokine level, and dosage and frequency of rescue medication. All adverse events and severe adverse events will be assessed during the study.ConclusionThis study is expected to provide evidence for the efficacy and safety of IFN-α1b injection into the intervertebral foramen in patients with PHN.Clinical trial registrationhttps://www.chictr.org.cn/indexEN.html, identifier ChiCTR240008996.